[RETRACTED] SARCOPENIA AND INFLAMMATORY BOWEL DISEASE: DEVELOPMENTAL MECHANISMS AND PRACTICAL IMPLICATIONS: This article has been retracted. The editorial board of the journal has determined that the article contains textual borrowings that are translations of foreign-language articles (parts thereof) without appropriate references to them. The decision to retract the article is based on the international COPE guidelines and was made in accordance with the publication ethics and editorial policy of the journal. The corresponding author agreed to the retraction of the article. - Romanukha, Viktoriya; Hryniv, Olena; Skrypnyk, Liubov; Malinina, Nataliia; Cherniavska, Iryna (Eastern Ukrainian Medical Journal, 2025)
Introduction. Sarcopenia is a generalised and progressive decline in skeletal muscle mass, strength and performance, leading to a reduction in quality of life, increased risk of falls and fractures, hospitalisation and mortality. While primary sarcopenia is a natural manifestation of ageing, secondary loss of muscle strength and mass can occur in many acute or chronic pathological conditions and is associated with a poor prognosis. Currently, there is growing interest in premature sarcopenia, which occurs in the setting of acute and chronic inflammatory processes, including inflammatory bowel disease. Materials and methods. The literature review was based on scientific studies published by Science Direct using the information retrieval systems PubMed, Web of Science, Scopus, Google Scholar, The Cochrane Library, Medknow. The research was mainly reviewed for the last 5 years. A total of 65 scientific papers were selected for this article. Results. Published studies suggest an association between sarcopenia and disease activity, the need for surgical treatment and adverse postoperative outcomes. Sarcopenia occurs in 20–70% of patients with inflammatory bowel disease. In recent years, the diagnosis of nutritional status disorders in patients with inflammatory bowel disease has changed due to the prevalence of obesity. Sarcopenia in such patients may occur in the setting of obesity and remain undiagnosed for a long time. Conclusions. Sarcopenia is associated with high activity and higher incidence of postoperative complications in patients with IBD and is an independent predictor of surgical intervention. Sarcopenic obesity is one of the features of the modern phenotype of a patient with inflammation bowel disease. Early diagnosis, prevention and treatment of sarcopenia and malnutrition in patients with inflammation bowel disease are likely to become one of the therapeutic goals in the future, in addition to clinical and endoscopic remission of the disease.